Phenotypic and Functional Diversity in Regulatory T Cells - Sjaastad, Louisa E.; Owen, David L.; Tracy, Sean I.; Farrar, Michael A. (Frontiers in Cell and Developmental Biology, 2021)
The concept that a subset of T cells exists that specifically suppresses immune responses was originally proposed over 50 years ago. It then took the next 30 years to solidify the concept of regulatory T cells (Tregs) into the paradigm we understand today – namely a subset of CD4+FOXP3+ T-cells that are critical for controlling immune responses to self and commensal or environmental antigens that also play key roles in promoting tissue homeostasis and repair. Expression of the transcription factor, FOXP3, and the cytokine IL-2, are necessary for Treg development and function, and defines this lineage. While our initial conception of Tregs was as a monomorphic lineage required to suppress all types of immune responses, recent work has demonstrated extensive phenotypic and functional diversity within the Treg population. In this review we address the ontogeny, phenotype, and function of the large number of distinct effector Treg subsets that have been defined over the last 15 years.